2020
DOI: 10.1111/1471-0528.16083
|View full text |Cite
|
Sign up to set email alerts
|

Risk of preterm birth after prior term cesarean

Abstract: Objective To determine the risk of overall preterm birth (PTB) and spontaneous PTB in a pregnancy after a caesarean section (CS) at term. Design Longitudinal linked national cohort study. Setting The Dutch Perinatal Registry (1999–2009). Population 268 495 women with two subsequent singleton pregnancies were identified. Methods A cohort study based on linked registered data from two subsequent pregnancies in the Netherlands. Main outcome measures The incidence of overall PTB and spontaneous PTB with subgroup a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A Dutch population study found that overall caesarean births at term was associated with a small increased risk in preterm birth, compared with vaginal birth, and this was mainly driven by an increase in spontaneous preterm birth. However, the study did not differentiate between the stage of labour at which the caesarean section was performed 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Dutch population study found that overall caesarean births at term was associated with a small increased risk in preterm birth, compared with vaginal birth, and this was mainly driven by an increase in spontaneous preterm birth. However, the study did not differentiate between the stage of labour at which the caesarean section was performed 7 …”
Section: Discussionmentioning
confidence: 99%
“…A number of risk factors have been associated with preterm birth including nulliparity, previous preterm birth, cervical surgery, short interpregnancy interval, social deprivation and smoking 4 . Caesarean delivery has been associated with preterm birth in a subsequent pregnancy in some studies, 5–7 but not others 8,9 . The stage in labour at which the caesarean section is performed may be crucial, with some studies suggesting preterm birth risk is higher if the caesarean section is performed in the second stage of labour, when the cervix is fully (10 cm) dilated, compared with caesarean before labour onset 2,5,10–12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the codes included in this visit indicate a long-term and current use of aspirin during the previous pregnancy, probably to prevent preterm preeclampsia. Moreover, the codes on this visit report that this patient had a previous cesarean delivery, which might also increase the risk of preterm birth in later pregnancies [ 37 , 38 ]. This patient is a great example demonstrating the ability of the attention mechanism to go beyond recent events and model long-range dependencies among medical events to the predicted outcome.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…In addition, the codes included in this visit indicate a long-term and current use of aspirin during the previous pregnancy, probably to prevent preterm preeclampsia. Moreover, the codes on this visit report that this patient had a previous cesarean delivery, which might also increase the risk of preterm birth in later pregnancies [34,35]. This patient is a great example demonstrating the ability of the attention mechanism to go beyond recent events and model longrange dependencies among medical events to the predicted outcome.…”
Section: Code-level and Visit-level Interpretationsmentioning
confidence: 93%